Intensitas Penggunaan Media Sosial Instagram Terhadap Body Image - Uswatun Hasanah; Beti Malia Rahma Hidayati (IDEA: Jurnal Psikologi, 2021)
This research aims to find out whether the Effect of The Intensity of Instagram Social Media Use On Body Image In Darul 'Ulum Jombang University Students. The population in this study was Darul 'Ulum Jombang University Student. The study sample of 100 students and sampling techniques used were Purposive Random Sampling, Body Image Scale and the intensity of Instagram social media use which was then analyzed using the SPSS program (Statistiscal Package For Social Sciences), corralate bivariaet program menu obtained correlation index value r rho = 0.539 Sig by 0.000 (p<0.01). This indicates a positive koleration between Instagram's Social Media Usage Intensity and Body Image. So the hypothesis is accepted.